THE EVOLUTION OF CONTEMPORARY BRITISH FICTION - Fayzieva Malika Sadikovna (Modern American Journals, 2025)
By the late 1980s, the influence of postmodernism in British literature had begun to decline. This observation is supported by scholars from England as well as from Russia and other European countries.